Towards a standardized e-assessment system: motivations, challenges and first findings - AL-Smadi, M.; Guetl, Christian; Helic, D. (International Association of Online Engineering, 2009)
"Global Learning" with shared learning contents, resources, activities and goals is one of the contributions of Globalization. With the capability to use new Information and Communication Technologies (ICT) it is a bit easier to have a technology based learning systems that enable learners to share the learning resources and possibilities. As a result many Learning Management Systems (LMS) were developed with divers of platforms and approaches. Consequently, sharing learning resources and components has become a major challenge. E-assessment as a primary activity of any LMS is facing the same challenges and problems. In order to stand on this challenge people in the field of technology enhanced learning have recommended that LMS should conform to specific standards. This paper discuses this challenge, the consequences and limitations of standards in the modern learning settings and shows our first service oriented approach which aims to make our e-assessment system flexible and also to initiate the term of "Global Learning Assessment" with the possibility of sharing the e-assessment system components.